2017
DOI: 10.21010/ajtcam.v14i2.28
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Efficacy of Extracts From Plants Used by Small-Holder Farmers in the Treatment of Dermatophilosis in Cattle

Abstract: Background: Bovine dermatophilosis, an important skin disease of cattle caused by Dermatophilus congolensis, negatively impacts the livelihoods of small-holder farmers in Zimbabwe. This impact is through, morbidity, loss of draught animal power, costs incurred to manage the disease, losses associated with devalued damaged hides and the resultant culling of some of the affected cattle. Due to the inaccessibility of conventional drugs to manage bovine dermatophilosis, farmers have been reported to use local medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…we have shown that fluctuations in the parameters of specific immunobiological protection occur throughout the period of lactogenesis. similar studies were obtained in studies (Singh et al, 2011;Thompson-Crispi et al, 2014;Ndhlovu & Masika, 2017;Sato et al, 2017;Powell et al, 2018;Piñeiro et al, 2019). We have shown that during lactation in the body of cows, both quantitative changes in the population of immunocompetent cells and changes in their functional activity occur (Zhelavskyi & Shunin, 2017;Zhelavskyi, 2017;Zhelavskyi et al, 2019).…”
Section: Resultssupporting
confidence: 66%
“…we have shown that fluctuations in the parameters of specific immunobiological protection occur throughout the period of lactogenesis. similar studies were obtained in studies (Singh et al, 2011;Thompson-Crispi et al, 2014;Ndhlovu & Masika, 2017;Sato et al, 2017;Powell et al, 2018;Piñeiro et al, 2019). We have shown that during lactation in the body of cows, both quantitative changes in the population of immunocompetent cells and changes in their functional activity occur (Zhelavskyi & Shunin, 2017;Zhelavskyi, 2017;Zhelavskyi et al, 2019).…”
Section: Resultssupporting
confidence: 66%
“…Significant difficulties were the definition of subclinical mastitis in the early period of lactation. The study of colostrum and secretion of the mammary gland in the final period of lactation (Zhelavskyi, 2007;Yablonskyi and Zhelavskyi, 2009;Ndhlovu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular and humoral immune defense factors that underlie the body's immune homeostasis reflect the state of regulatory and effector mechanisms of immune defense (Yablonskyi and Zhelavskyi, 2008;Blum et al, 2015;Kempf et al, 2016;Lombardini et al, 2017;Ndhlovu and Masika, 2017;Cao et al, 2018). The studies carried out in this direction have shown that the parameters of immune homeostasis change in the pathogenesis of mastitis.…”
Section: Resultsmentioning
confidence: 99%